2006
DOI: 10.5344/ajev.2006.57.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Wine Phenolics: A Critical Evaluation and Hypotheses

Abstract: symposium articles were peer reviewed by two fellow presenters, and James Harbertson, Mark Downey, and Sara Spayd served as technical editors of the articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(62 citation statements)
references
References 43 publications
(26 reference statements)
1
48
0
Order By: Relevance
“…These results indicated that the samples consumed all the available oxygen quickly, developing more reactions with oxygen by generating highly oxidizable compounds. This may be due to the reactions that occur once oxygen is reduced to hydrogen peroxide [ 58 ] with the Fenton reaction [ 59 ]. This peroxide can react with ferrous or cuprous ions and form hydroxyl radicals capable of oxidizing ethanol to acetaldehyde [ 54 , 60 ], which reacts with numerous compounds, such as anthocyanins generating more stable and complex phenolic compounds [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the samples consumed all the available oxygen quickly, developing more reactions with oxygen by generating highly oxidizable compounds. This may be due to the reactions that occur once oxygen is reduced to hydrogen peroxide [ 58 ] with the Fenton reaction [ 59 ]. This peroxide can react with ferrous or cuprous ions and form hydroxyl radicals capable of oxidizing ethanol to acetaldehyde [ 54 , 60 ], which reacts with numerous compounds, such as anthocyanins generating more stable and complex phenolic compounds [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, HCA participates in the formation of new anthocyanin-derived pigments in wine, known as hydroxyphenyl-pyranoanthocyanins. Moreover, GA seems to be stable along the wine aging process [ 68 ], and the prefermentative addition of GA at appropriate levels might be a promising enological technology to obtain wines with high color quality and aging potential [ 68 , 69 ]. In this sense, it is important to highlight that varieties such as ‘Evega 3’, ‘Evega 6’, and ‘Corbillón’ showed higher quantities in both years than the mean content found in the ‘Tempranillo’ reference variety, grown in the same edaphoclimatic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, many connoisseurs prefer a longer period of aging. Of course, the sensitivity of a red wine to oxygen depends significantly on its phenolic, antioxidant, and transition-metal contents, whereas its aging potential (AP) is also influenced by the amount of oxygen imparted during bottle aging. , Unfortunately, the impact of stoppers on the long-term aging of red wines has not been widely documented till date. As in a recently published study on white wines, we evaluated the sensory and composition evolution of three red wines from Bordeaux selected for their intrinsic qualities as a function of closure type over a period of 10 years.…”
Section: Introductionmentioning
confidence: 99%